Electrochemical biosensor based on Cu/Cu2O nanocrystals and reduced graphene oxide nanocomposite for sensitively detecting ractopamine. (10th November 2015) - Wang, Minghua; Kang, Mengmeng; Guo, Chuanpan; Fang, Shaoming; He, Linghao; Jia, Chunxiao; Zhang, Gaihong; Bai, Bing; Zong, Wei; Zhang, Zhihong
Abstract: Three-dimensional nanocomposite of reduced oxide graphene (rGO) and Cu/Cu2 O nanocrystal (3D Cu/Cu2 O@rGO) was synthesized via a one-step low-temperature co-reduction method and further used as an electrochemical sensor for detecting ractopamine (RAC). In comparison with pristine Cu2 O nanospheres and porous rGO, ractopamine antibody (RACanti ) prefers to anchor onto the surface of 3D Cu/Cu2 O@rGO nanocomposite because of its multi-functionality, which subsequently leads to more sensitive RAC detection. The developed electrochemical biosensor based on 3D Cu/Cu2 O@rGO nanocomposite adsorbed with RACanti showed a low detection limit of 7.5 pg mL −1 within the range of 0.1 ng mL −1 to 10 ng mL −1 for detecting RAC. Furthermore, interference from other lean meat powders, urine components, and metal ions, such as salbutamol, clenbuterol hydrochloride, uric acid, urea, K +, Na +, Mg 2+, and Ca 2+, associated with RAC analysis can be effectively inhibited. The strategy offers a new pathway for rapid RAC analysis and shows a promising prospect in food safety.